Edukasi influenza dan virus Nipah untuk pencegahan infeksi saluran pernapasan - Arief Rahman; Ero Ari Angga; Lalu Ramadlan; Intan Nefia Alamanda; Andi Nizam Harahap; Yosilia Nursakina; Hartini Haritani; Sitti Rohmi Djalilah (Universitas Hamzanwadi, 2026)
Influenza is one of the acute respiratory infections that remains a public health concern due to its high transmissibility and potential to cause complications, particularly among vulnerable groups. In addition to seasonal influenza, the term “Super Flu” has become increasingly common in public discussions and social media, which may cause concern and misunderstanding regarding influenza. Meanwhile, Nipah virus infection is a zoonotic disease that can cause respiratory and neurological manifestations with a high fatality rate. This community service activity aimed to improve public knowledge of influenza, the term “Super Flu,” and Nipah virus infection, as well as their prevention. The activity was conducted in February 2026 at the Birrul Walidain NWDI Hall, Pancor, East Lombok Regency, involving 86 members of Muslimat NWDI, West Nusa Tenggara. Health education was delivered through lectures, interactive discussions, and question-and-answer sessions. Participants’ knowledge was assessed using pre-test and post-test questionnaires. The results showed an increase in knowledge following the activity. The proportion of participants with good knowledge increased from 21 participants (24.4%) in the pre-test to 68 participants (79.1%) in the post-test, while the proportion with poor knowledge decreased from 26 participants (30.3%) to 3 participants (3.5%). Improvements in knowledge were also observed across all age and educational groups. The activity suggests that direct and interactive health education can help participants better understand information about influenza, “Super Flu,” Nipah virus infection, and preventive measures. Similar educational activities can be conducted continuously with more structured evaluation to strengthen efforts to promote and prevent respiratory infectious diseases.